WHAT IS THERAPEUTIC EQUIVALENCE OF GENERIC DRUG AND HOW TO PROVE IT - N. P. Kutishenko; S. Yu. Martsevich; I. V. Vashurina (Рациональная фармакотерапия в кардиологии, 2016)
The problem of generic drugs use in clinical practice and confirmation of their therapeutic equivalence is discussed. The significance of studies on generic drugs bioequivalence, as well as details of international practice and regulations in this area is explained.